Gastrointestinal involvement in systemic mastocytosis. - R Ammann; D Vetter; P Deyhle; H Tschen; H Sulser; M Schmid (1976)
Four consecutive patients with systemic mastocytosis were studied. One patient had a malabsorption syndrome with only minor histological changes of the intestinal mucosa. Another patient with ulcer diathesis had a gastric secretory pattern resembling Zollinger-Ellison syndrome. Serum gastrin and histamine levels were consistently normal in all patients. Endoscopy of stomach and colon disclosed urticaria-like papulae either spontaneously or after topical provocation in all patients. No increase of mast cells was found in multiple mucosal biopsies. A markedly increased gastric tissue content of histamine was found, however, in the three patients studied. The findings suggest that urticaria-like lesions associated with a high tissue content of histamine may be more important that hyperhistaminaemia in causing the various gastrointestinal symptoms.